Injuries in professional dancers: A systematic review Lesões em bailarinos profissionais: Uma revisão sistemática Lesiones en los bailarines profesionales: Una revisión sistemática - Cardoso A.A.* (2017)
© 2017, Redprint Editora Ltda. All rights reserved.Movement is a fundamental element of dance, and the dancer’s body is the raw material through which the art of dance is expressed; for this, it demands the utmost discipline in the pursuit of technical and artistic excellence. To meet the professional demands, dancers are subjected to strenuous training routines, which can lead to the development of injuries in this environment. The objective was to examine the etiology, main affected segments, prevalence, and instruments used to evaluate the lesions in studies with professional dancers and/or in comparison with similar populations. We selected articles published in the last decade in the databases BIREME, LILACS, MEDLINE EBSCO, WEB OF SCIENCE, SCOPUS (Elsevier), and PubMed, with cross-sectional, observational cohort and case control design published in Portuguese, English, or Spanish. Systematic reviews, case studies, dissertations, theses, book chapters, cross-referenced articles, and studies published outside of the last decade were not included. The search used combinations of the terms “dancing* and athletic injuries* and musculoskeletal* and pain*". A principal investigator and two reviewers conducted the survey and analyzed all the potentially relevant articles, initially by the abstract and title. Twelve articles were included, with 1,149 participants (965 professional dancers of classical ballet, modern dance, contemporary dance, and breakdance, 104 amateur dancers, and 80 elite athletes). Nine studies found simultaneous lesions with emphasis on the foot and ankle (n=4), upper and lower limbs lesions (n=4) and lower and upper limb joints (n=1). Other studies have found lesions in the anterior cruciate ligament (n=3). There was no agreement regarding the instruments for detecting lesions in professional, pre-professional, and amateur dancers. There was a prevalence of studies aimed at classical ballet modality, evidencing a higher frequency of lower limb involvement in professional dancers.